Overprinting mineralization in the Paleozoic Yandong porphyry copper deposit, Eastern Tianshan, NW China-Evidence from geology, fluid inclusions and geochronology - Wang, Y.; Chen, H.; Xiao, B.; Han, J.; Fang, J.; Yang, J.; Jourdan, Fred (Elsevier Science BV, 2016)
The Yandong porphyry copper deposit is located in the southern part of the Dananhu-Tousuquan Island Arc belt in Eastern Tianshan (Xinjiang, NW China). The Dananhu-Tousuquan belt contains a number of large and medium Cu deposits, among which the Yandong deposit (~2.0 Mt Cu @ 0.67%) is the largest. The Yandong Cu deposit is hosted by plagiogranite porphyry and the Carboniferous Qi'eshan Group mafic to intermediate calc-alkaline volcanic and pyroclastic rocks. According to the crosscutting relationships and mineral assemblages, the alteration and mineralization processes at Yandong comprise three episodes: the porphyry mineralization episode (including potassic, propylitic, early phyllic and late phyllic stages), the overprinting mineralization episode (including main- and post-mineralization stages) and lastly supergene alteration episode. Fluid inclusions (FIs) in quartz from the potassic, early/late phyllic and post-mineralization stages, and anhydrite from the main-/post-mineralization stages include four types: 1) vapor-liquid two phases (W-type), 2) daughter mineral-bearing (S-type), 3) pure liquid (PW-type), and 4) pure vapor (PV-type). The potassic stage contains W-, S- and PV-type FIs, which yielded homogenization temperatures of 304-445. °C (mainly 340-400. °C) and salinities of 3.1-16.4 (mainly 4.0-10.0). wt% NaCl eqv. At the early phyllic stage, three types of FIs are identified, i.e., the W-, S-, and PV-type. The S-type and W-type FIs homogenized at 213-441. °C (mainly 280-300. °C) and 241-352. °C (mainly 300-320. °C), respectively, with corresponding salinities of 33.1-52.0 (mainly 34.0-40.0). wt% NaCl eqv. and 0.9-15.9 (mainly 0.9-4.0). wt% NaCl eqv., respectively. The late phyllic stage contains W-, S- and PW-type FIs, which homogenized at 146-248. °C (mainly 160-180. °C), with salinities ranging from 3.9 to 18.2 (mainly 4.0-8.0). wt% NaCl eqv.Mineralization depths calculated from FIs are: 0.8-1.2. km (Stage I), 0.6-1.8. km (Stage IIIA) and 0.4-0.7. km (Stage IIIB). Fluid boiling and mixing likely occurred during the porphyry mineralization period, leading to the precipitation of pyrite and chalcopyrite. During the overprinting mineralization, the W- and PV-type FIs occur in the main-mineralization anhydrite, with homogenization temperatures and salinities being 248-421. °C (mainly 300-340. °C) and 5.3-13.8 (mainly 8.0-10.0). wt% NaCl eqv., respectively. The post-mineralization quartz and anhydrite homogenized at 105-195. °C (mainly 120-140. °C), with salinities of 0.5-13.6 (mainly 8.0-10.0). wt% NaCl eqv. The ore-forming fluids may have predominantly been entrapped at 0.8-1.6. km (Stage IV) and 0.3-0.6. km (Stage V). The decreasing temperature may have led to the sulfides and sulfate precipitation and enrichment.Sericite 40Ar/39Ar dating of the altered plagiogranite porphyry yielded a plateau age of 332.8±3.8Ma, consistent with the age of the early ore-forming plagiogranite porphyry (339-332Ma). Re-Os dating of molybdenite, coexisting with chalcopyrite-anhydrite-chlorite-calcite assemblage, yielded an age of 324.3±2.7Ma (weighted mean), consistent with the late quartz albite porphyry age (zircon U-Pb: 323.6±2.5Ma).Consequently, we propose that at least two mineralization episodes may have occurred at Yandong, with the second episode contributing to the majority of the Cu-Mo resources. Such overprinting mineralization style at Yandong may represent a good example of the Paleozoic Cu deposits in the Central Asian Orogenic Belt.